The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1002/pbc.25312
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for abandonment of Wilms tumor therapy in Kenya

Abstract: Background Survival from Wilms tumor (WT) in sub-Saharan Africa remains dismal as a result of on-therapy mortality and treatment abandonment. Review of patients diagnosed from 2008–2011 in our Kenyan Wilms Tumor Registry showed a loss to follow up (LTFU) rate approaching 50 percent. The purpose of this study was to trace those LTFU, estimate the survival rate, and identify risk factors for treatment abandonment. Procedure We administered a comprehensive survey to parents of patients with WT at the two larges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 21 publications
4
40
1
Order By: Relevance
“…Seven studies were excluded; a full list of these and the reasons for exclusion are shown in the supplementary material. All studies were cohort studies, four were single‐centre (Mostert et al., ; Mtete et al., ; Njuguna et al., ; Slone et al., ) and two multi‐centre (Axt et al., ; Libes et al., ). The countries where the studies took place were Kenya (Axt et al., ; Libes et al., ; Mostert et al., ; Njuguna et al., ), Malawi (Mtete et al., ) and Zambia (Slone et al., ).…”
Section: The Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Seven studies were excluded; a full list of these and the reasons for exclusion are shown in the supplementary material. All studies were cohort studies, four were single‐centre (Mostert et al., ; Mtete et al., ; Njuguna et al., ; Slone et al., ) and two multi‐centre (Axt et al., ; Libes et al., ). The countries where the studies took place were Kenya (Axt et al., ; Libes et al., ; Mostert et al., ; Njuguna et al., ), Malawi (Mtete et al., ) and Zambia (Slone et al., ).…”
Section: The Reviewmentioning
confidence: 99%
“…The risk of bias in each study was assessed using the Newcastle‐Ottawa Scale, the summary of the findings is shown in Table . Briefly, all studies scored highly for selection apart from one where the comparison cohort had different forms of cancer (Mtete et al., ); for comparability two studies had no comparison group at all meaning only proportions could be calculated (Libes et al., ; Njuguna et al., ); and all studies had large loss of subjects of unknown significance. Two studies also used self‐report measures (Libes et al., ; Njuguna et al., ), although as this subject has high saliency and this is an appropriate way of collecting these data, no reduction was made for this.…”
Section: The Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 In developing countries, patients refused or abandoned treatment due to logistical, financial, or social reasons, such as distance from the hospital and difficult physician-patient relationships due to social background or inadequate health insurance. [6][7][8][9] A recent survey of respondents from the 101 mostly low-and middleincome countries revealed a rate of treatment abandonment of 15%. 5 In El Salvador, a treatment refusal rate of 13% was determined from a sample of 612 patients with cancer, under 16 years of age, within the given investigation period; in Indonesia, 35% of 164 patients with acute lymphoblastic leukemia (ALL) refused or abandoned treatment.…”
Section: Gpoh Closely Collaborates With the Population-based Germanmentioning
confidence: 99%
“…Although overall survival rates had improved, treatment refusal and treatment abandonment have been described in developing as well as high‐income countries . In developing countries, patients refused or abandoned treatment due to logistical, financial, or social reasons, such as distance from the hospital and difficult physician–patient relationships due to social background or inadequate health insurance . A recent survey of respondents from the 101 mostly low‐ and middle‐income countries revealed a rate of treatment abandonment of 15% .…”
Section: Introductionmentioning
confidence: 99%